Working from home around the globe: 2023 Report - Cevat Giray Aksoy; Jose Maria Barrero; Nicholas Bloom; Steven J. Davis; Mathias Dolls; Pablo Zarate (CESifo GmbH, 2023)
How prevalent is remote work on a global scale? What are the prevailing modes of working arrangements at present? What are the foremost advantages of working from home and on employer's business premises? Is there a need for policy intervention? Our new Global Survey of Working Arrangements provides new insights to answer these questions.
Keywords: 330; Telearbeit; Vergleich; Welt